Molecular Detection of Pseudorabies Virus (PrV), Porcine Parvovirus (PPV) and Porcine Circovirus 2 (PCV2) in Swine in Republic of Montenegro - Miković Radoš (Sciendo, 2016)
The presence of pseudorabies virus (PrV), porcine parvovirus (PPV) and porcine circovirus 2 (PCV2) was examined in sixty samples (spleen and lymph nodes) and thirty samples of sacral ganglia collected from non-vaccinated swine by virus isolation and polymerase chain reaction (PCR). Using PCR method PrV was detected in three samples, PPV in seven samples and six samples were found positive for PCV2. The phylogenetic analysis of the nucleotide sequences of three PrV isolates identified in this study showed high similarity and significant clustering within the PrV genotype I strains such as Kaplan and Bartha isolated from pigs in Hungary, strain Becker isolated in USA and strain Kolchis isolated in Greece. The nucleotide sequences of two PPV isolates showed high level of similarity with the strain Challenge isolated from pigs in UK, strain Kresse isolated in USA and strains 77 and LZ isolated in China. The phylogenetic analysis of the nucleotide sequences of two PCV2 isolates showed high level of similarity and significant clustering within genotype PCV2b strains such as NIVS-3, NIVS-5 and NIVS-6 isolated in Serbia, strain 3959 isolated in Austria, strain PM165 isolated from pigs in Brasil, and strain XT2008 isolated in China. The results of our study present the molecular characterization of PrV, PPV and PCV2 identified in swine in Republic of Montenegro. Besides that, these results confirmed that PCR is a very useful method for rapid detection of these viruses in subclinically infected swine.